"CRYPTOGENIC DROP ATTACKS" REVISITED. Issue 12 (15th November 2016) - Hoeritzauer, Ingrid; Carson, Alan; Stone, Jon
Abstract : Background: Drop attacks are idiopathic falls occurring predominantly in middle aged women without warning, not due to change in posture or head movement associated with immediate recovery. Drop attacks have been attributed to cardiovascular, structural, musculoskeletal, epileptic, vestibular and (very rarely) functional/ psychogenic causes. Methods: Notes review of a consecutive case series of patients with drop attacks seen by one of the authors (JS) in a neurology setting. Results: Preliminary data demonstrates that of 88 patients with drop attacks 79 were female, mean age 44 (range 16–78), mean duration of attacks 61 months (1–388). Secondary drop attacks were recorded rarely (n=2, cataplexy, Chiari malformation). Dissociative symptoms during a brief prodrome (n=40) and after the attack (n=9) were common. Characteristically, patients did not recall the fall itself. Twenty six patients had episodes of dissociation unrelated to their drop attacks (n=19 dissociative seizures with loss of consciousness, n=14 had dissociation with preserved consciousness). There were high levels of fatigue (n=61), sleep disturbance (n=59), chronic pain (n=40) and comorbid functional neurological disorders (n=51). Some patients improved with techniques used in dissociative seizures. Conclusions: Idiopathic drop attacks may be best understood in many cases as a type of functional disorder.